2008
DOI: 10.1016/j.neuroscience.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of GLT1 expression increases glutamate uptake and attenuates the Huntington's disease phenotype in the R6/2 mouse

Abstract: The striatum, which processes cortical information for behavioral output, is a key target of Huntington's disease (HD), an autosomal dominant condition characterized by cognitive decline and progressive loss of motor control. Increasing evidence implicates deficient glutamate uptake caused by a down-regulation of GLT1, the primary astroglial glutamate transporter. To test this hypothesis, we administered ceftriaxone, a beta-lactam antibiotic known to elevate GLT1 expression (200 mg/kg, i.p., for 5 days), to sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
270
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(279 citation statements)
references
References 53 publications
7
270
0
2
Order By: Relevance
“…Consistent with this view, we found that chronic treatment with Cef (i.p., 200 mg/kg) not only increased GLT-1 expression in LA but also reversed the impairment of LTP and fear memory in AQP4 KO mice. Our behavioral test indicated that Cef did not alter locomotor activity or pain thresholds of mice (data not shown), which was consistent with previous reports (Miller et al, 2008;Rothstein et al, 2005). Thus, accelerated clearance of extracellular glutamate appears to underlie the ability of Cef to reverse the impairment of LTP and fear memory.…”
Section: Aqp4 Regulates Amygdala Ltp and Memory Y-k LI Et Alsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with this view, we found that chronic treatment with Cef (i.p., 200 mg/kg) not only increased GLT-1 expression in LA but also reversed the impairment of LTP and fear memory in AQP4 KO mice. Our behavioral test indicated that Cef did not alter locomotor activity or pain thresholds of mice (data not shown), which was consistent with previous reports (Miller et al, 2008;Rothstein et al, 2005). Thus, accelerated clearance of extracellular glutamate appears to underlie the ability of Cef to reverse the impairment of LTP and fear memory.…”
Section: Aqp4 Regulates Amygdala Ltp and Memory Y-k LI Et Alsupporting
confidence: 92%
“…It is well known that Cef, one of the b-lactam antibiotics, increases expression and activity of GLT-1 (Rothstein et al, 2005). Previous studies have shown that single daily injection of Cef (200 mg/kg) for 5-7 days increases the GLT-1 expression and glutamate uptake in both the cortex and the striatum, as well as in the nucleus accumbens (Knackstedt et al, 2010;Miller et al, 2008;Sari et al, 2010). Therefore, the Cef-induced increase in GLT-1 expression has a direct effect on glutamate function.…”
Section: Aqp4 Regulates Amygdala Ltp and Memory Y-k LI Et Almentioning
confidence: 99%
“…Ceftriaxone attenuated paw clasping and improved motor flexibility (as measured in a plus maze test, and an open-field apparatus). As expected, ceftriaxone induced an increase in striatal GLT1 expression and consequently reversed the deficit in glutamate uptake characteristic of these mice (assessed by microdialysis) (Miller et al, 2008). Given these promising results, future studies should investigate whether ceftriaxone treatment (i.e., an increase in glutamate uptake by the glial cells) will also have a long-term effect on the behavior and neuropathology of R6/2 mice.…”
Section: Inhibition Of Excitotoxicitysupporting
confidence: 52%
“…Thus, Miller et al (2008) have recently tested the effects of ceftriaxone, a betalactam antibiotic known to elevate GLT1 expression. Ceftriaxone was administered to symptomatic 6 week-old R6/2 mice and the animals were submitted to behavioral testing for 7 days after receiving the last drug injection.…”
Section: Inhibition Of Excitotoxicitymentioning
confidence: 99%
“…Pre-clinical studies performed thus far utilizing the rotarod, plus maze and open field locomotion tests demonstrated that GLT-1 up-regulation does not alter motor or cognitive function [18,33]. More sophisticated tests of motor, cognitive and neuronal function will be required.…”
Section: Translational Potential Of Glt-1 Up-regulation In the Treatmmentioning
confidence: 99%